2005
DOI: 10.1111/j.1745-4514.2005.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenoloxidase Activity, Browning Potential and Phenolic Content of Peaches During Postharvest Ripening

Abstract: Changes in the polyphenoloxidase (PPO) activity and the phenolic content of peaches (Prunus persica cv. Premier) during postharvest ripening were studied. The fruits were stored at 12 or 25C for up to 15 days. The quantity of extractable proteins was maximum at 6-10 days storage at 25 and 12C, coinciding with the onset of the yellowness in the fruits. The PPO activity increased up to the ripening stage, showing a maximum value at 8 days of storage. This was coincident with the maximum degree of browning as eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
(36 reference statements)
3
20
0
5
Order By: Relevance
“…On the contrary, the concentration of hydroxycinnamic acids was in agreement with literature (Andreotti et al, 2008;Chang et al, 2000;Tomàs-Barberàn et al, 2001) ranging from 103 to 303 mg/kg in the pulp and from 193 to 682 mg/kg in the peel. In the other cases, the concentration of hydroxycinnamic acids found was less (Brandelli & Lopes, 2005). Phenolic compounds showed statistical differences among the landraces except for the flavan-3-ols in the pulp, while there were no statistical differences among the altitudes.…”
Section: Phenolic and Antioxidant Capacity Measurementmentioning
confidence: 69%
See 1 more Smart Citation
“…On the contrary, the concentration of hydroxycinnamic acids was in agreement with literature (Andreotti et al, 2008;Chang et al, 2000;Tomàs-Barberàn et al, 2001) ranging from 103 to 303 mg/kg in the pulp and from 193 to 682 mg/kg in the peel. In the other cases, the concentration of hydroxycinnamic acids found was less (Brandelli & Lopes, 2005). Phenolic compounds showed statistical differences among the landraces except for the flavan-3-ols in the pulp, while there were no statistical differences among the altitudes.…”
Section: Phenolic and Antioxidant Capacity Measurementmentioning
confidence: 69%
“…This fact is particularly evident for flavan-3-ols (Andreotti, Ravaglia, Ragaini, & Costa, 2008;Arts, van de Putte, & Hollman, 2000;Brandelli & Lopes, 2005;Chang, Tan, Frankel, & Barrett, 2000;Tomàs-Barberàn et al, 2001). Their concentrations ranged from 1160 to 2147 mg/kg in the pulp, and from 1342 to 4578 mg/kg in the peel.…”
Section: Phenolic and Antioxidant Capacity Measurementmentioning
confidence: 92%
“…Many studies with fresh or cut fruit and juice showed the relationships between browning and the polyphenol content and/or PPO activity (Brandelli and Lopes, 2005;Ding et al, 1998;Murata at al., 1995aMurata at al., , 1995bNguyen et al, 2003;Sannomaru et al, 1998). However, there has been no report that associated PPO and its substrate with browning during drying persimmon fruit, although the polyphenol or tannin content was often determined in relation to the removal of astringency (Ishii and Yamanishi, 1982;Taira et al, 1988).…”
Section: Experiments For Enzymatic Browning In 2005mentioning
confidence: 99%
“…Polyphenol oxidase (PPO) is one of the most important enzymes involved in the enzymatic browning of food, and a close relationship between the browning potential and PPO activity and/or polyphenol content was found in several fruits (Brandelli and Lopes, 2005;Ding et al, 1998;Murata et al, 1995aMurata et al, , 1995bNguyen et al, 2003). On the other hand, the oxidative and non-oxidative degradation of ascorbic acid (Kurata, 1976;Li et al, 1989;Shinoda et al, 2005) and the Maillard reaction (Bolin and Steele, 1987;Caglarirmak, 2006;Sanz et al, 125 2001) have also been suggested to play important roles in the discoloration of many foods including dried fruit as non-enzymatic browning.…”
Section: Introductionmentioning
confidence: 99%
“…O escurecimento enzimático em frutas e hortaliças minimamente processadas é na maioria das vezes indesejável sendo responsável pela perda da qualidade sensorial e nutricional do produto (Brandelli & Lopes, 2005). Essa reação, em consequência de um ferimento mecânico, é causada, principalmente, pela oxidação de compostos fenólicos catalisada pela polifenoloxidase (PFO) com sua subsequente polimerização por reações enzimáticas e não-enzimáticas (Robert et al, 1995).…”
unclassified